Pragmatic Interpretation of Emotional Utterances in Acehnese: Evidence from Students at Universitas Bumi Persada - Asmaul Husna; Ibnu Hajar; Sitti Aminah; Andriani Andriani; Cut Yuniza Eviyanti (English Education Study Program FKIP Universitas Alwashliyah Medan, 2026)
This study aims to interpret the pragmatic meanings of emotional utterances in Acehnese used by students at Universitas Bumi Persada during informal communication. The emotional categories examined include happiness, anger, sadness, disappointment, fear, embarrassment, and surprise/confusion. The study employed a qualitative approach using a descriptive research design. The data consisted of 36 emotional utterances collected through participant observation, audio recordings of naturally occurring conversations, and field notes. Data analysis was conducted using Searle's (1969) Speech Act Theory, Grice's (1975) Conversational Implicature Theory, Sperber and Wilson's (1995) Relevance Theory, and Leech's (1983) Politeness Principle. The findings reveal that emotional utterances in Acehnese are not always expressed explicitly but are frequently conveyed through conversational implicatures, indirect expressions, and politeness strategies such as humility, reassurance, and avoidance. The pragmatic meanings of these utterances are constructed through inferential processes that rely on communicative context, interpersonal relationships, and shared knowledge. These findings demonstrate that Acehnese functions not only as a means of communication but also as a medium for expressing emotions and maintaining social harmony in students' interactions. Keywords: Acehnese, emotional utterances, politeness, pragmatics, speech acts